Prentice Hall science North Carolina integrated science (New Jersey : Prentice Hall, 2000)
Prentice Hall science explorer "Customized to meet the North Carolina [curriculum] standards .
includes glossary and index.
Keywords: Science -- Juvenile literature; Science